1=y+3(y-9)

Simple and best practice solution for 1=y+3(y-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1=y+3(y-9) equation:


Simplifying
1 = y + 3(y + -9)

Reorder the terms:
1 = y + 3(-9 + y)
1 = y + (-9 * 3 + y * 3)
1 = y + (-27 + 3y)

Reorder the terms:
1 = -27 + y + 3y

Combine like terms: y + 3y = 4y
1 = -27 + 4y

Solving
1 = -27 + 4y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-4y' to each side of the equation.
1 + -4y = -27 + 4y + -4y

Combine like terms: 4y + -4y = 0
1 + -4y = -27 + 0
1 + -4y = -27

Add '-1' to each side of the equation.
1 + -1 + -4y = -27 + -1

Combine like terms: 1 + -1 = 0
0 + -4y = -27 + -1
-4y = -27 + -1

Combine like terms: -27 + -1 = -28
-4y = -28

Divide each side by '-4'.
y = 7

Simplifying
y = 7

See similar equations:

| 2.4=2.7 | | 25p^2-49p-2=0 | | 6(x+3)=3(2x+9)-9 | | 14x^2y^2+68xy^2-210y^2=0 | | 17k-12-4k-16k= | | 45z^2+56z-45=0 | | 4(0)+-2=-2 | | 10x-26=264 | | 3x-8x= | | 21b^2-114b-72=0 | | 87=5n-23 | | .12(18)+0.03x=0.06(24+x) | | 10x=264 | | 37=x+48 | | 18m^2-77m-18=0 | | 3(0)=-y+3 | | 3-8h=35 | | 13-x=-8 | | 3(-2)=-y+3 | | 8x^2-46xy+11y^2=0 | | 30-3x=2+x | | 2m^2+13m+10=0 | | 2m^2-10-4=4 | | .5x+12=27 | | 16x-3y=18 | | 12x^2+133x+11=0 | | 350-167+v=2v | | 68+2x-30=x+42 | | Y+(-8)=-23 | | 24-x=42 | | 4x+5=2(3x+25) | | 6x-2=2x-10 |

Equations solver categories